Evaluation of the effectiveness of occlusal splint therapy and exercise therapy on temporomandibular disorders: A systematic review - Cahyani, Irvi; Chairunnisa, Ricca; Norasmatul Akma, Ahmad (Padjadjaran Journal of Dental Researchers and Students, 2024)
ABSTRACTIntroduction: Temporomandibular disorders (TMD) involve the temporomandibular joint, masticatory muscles, and associated structures, presenting with various symptoms such as difficulty in chewing, speaking, and other orofacial functions. Common treatment options for TMD include occlusal splint therapy and exercise therapy. This study aims to evaluate the effectiveness of occlusal splint therapy and exercise therapy in managing TMD through a systematic review. Methods: Literature searches were conducted in PubMed, ProQuest, and Google Scholar, covering publications from 2012 to 2022. The keywords used included ("temporomandibular disorders") AND (exercise OR physiotherapy OR "exercise therapy") AND ("splints" OR "occlusal splints" OR "occlusal appliance" OR "occlusal splint therapy"). Data synthesis was performed using qualitative data analysis techniques. Results: Based on the search results, 1,707 articles were identified. After checking for duplicates and filtering according to PICOS and inclusion criteria, 7 articles were found to be eligible. From the results that had already been obtained and analyzed, occlusal splint therapy and physical exercise therapy had the same effectiveness but had their own advantages and disadvantages. Both therapies demonstrated a reduction in pain and improvement in limited mouth opening. Conclusion: There is no difference in the effectiveness of occlusal splint therapy and exercise therapy for managing TMD. Considering their respective benefits and limitations, exercise therapy may be recommended as an initial treatment for TMD, while occlusal splint therapy can be employed for specific pathological conditions or as a complementary treatment in advanced cases.KEY WORDS: temporomandibular disorders, occlusal splint therapy, exercise therapyEvaluasi efektivitas terapi splin oklusal dan terapi fisik latihan terhadap gangguan temporomandibular: systematic reviewABSTRAK Pendahuluan: Gangguan Temporomandibular (TMD) melibatkan sendi temporomandibular, otot pengunyahan, dan struktur terkait, dengan gejala seperti kesulitan mengunyah, berbicara, dan fungsi orofasial lainnya. Pilihan perawatan yang umum untuk TMD adalah terapi splin oklusal dan terapi latihan. Penelitian ini bertujuan untuk mengevaluasi efektivitas terapi splin oklusal dan terapi latihan dalam menangani TMD melalui tinjauan sistematis. Metode: Pencarian literatur dilakukan melalui PubMed, ProQuest, dan Google Scholar dengan cakupan publikasi dari tahun 2012 hingga 2022. Kata kunci yang digunakan meliputi: ("temporomandibular disorders") AND (exercise OR physiotherapy OR "exercise therapy") AND ("splints" OR "occlusal splints" OR "occlusal appliance" OR "occlusal splint therapy"). Sintesis data dilakukan menggunakan teknik analisis kualitatif. Hasil: Berdasarkan hasil pencarian, ditemukan 1.707 artikel. Setelah dilakukan pengecekan duplikasi dan penyaringan berdasarkan PICOS serta kriteria inklusi, diperoleh 7 artikel yang sesuai. Berdasarkan hasil yang sudah didapatkan dan dianalisis, terapi splin oklusal dan terapi fisik latihan memiliki efektivitas yang sama namun memiliki kelebihan dan kekurangannya masing-masing. Kedua terapi tersebut dapat memberikan hasil mengurangi rasa nyeri dan perbaikan keterbatasan pembukaan mulut. Simpulan: Tidak ditemukan perbedaan dalam efektivitas terapi splin oklusal dan terapi latihan untuk menangani TMD. Berdasarkan kelebihan dan keterbatasannya, terapi latihan dapat direkomendasikan sebagai perawatan awal untuk TMD, sementara terapi splin oklusal dapat digunakan untuk kondisi patologis tertentu atau sebagai perawatan tambahan pada kasus lanjut.KATA KUNCI: gangguan temporomandibular, terapi splin oklusal, terapi latihan